2017
DOI: 10.1186/s11689-017-9200-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses and characteristics of autism spectrum disorders in children with Prader-Willi syndrome

Abstract: BackgroundA small percentage of people with autism spectrum disorders (ASD) have alterations in chromosome 15q11.2-q3, the critical region for Prader-Willi syndrome (PWS). Data are limited, however, on the rates and characteristics of ASD in PWS. Previous estimates of ASD in PWS (25 to 41%) are questionable as they are based solely on autism screeners given to parents. Inaccurate diagnoses of ASD in PWS can mislead intervention and future research.MethodsOne hundred forty-six children and youth with PWS aged 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 56 publications
(63 reference statements)
5
54
1
Order By: Relevance
“…There were some differences in our PWS cohort in regards to distribution of genetic subtype and prevalence of ASD among subtypes than previously reported (Cassidy, Schwartz, Miller, & Driscoll, ). In regards to genetic subtype, more recent studies describe different trends in genotype distribution than classically reported (65–75% deletion, 20–30% mUPD, and 2–5% imprinting defect) with higher percentages of mUPD, similar to our distribution (Butler et al, ; Butler et al, ; Dykens et al, ). This may be a reflection of improved diagnostic methods and need for updated epidemiological studies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…There were some differences in our PWS cohort in regards to distribution of genetic subtype and prevalence of ASD among subtypes than previously reported (Cassidy, Schwartz, Miller, & Driscoll, ). In regards to genetic subtype, more recent studies describe different trends in genotype distribution than classically reported (65–75% deletion, 20–30% mUPD, and 2–5% imprinting defect) with higher percentages of mUPD, similar to our distribution (Butler et al, ; Butler et al, ; Dykens et al, ). This may be a reflection of improved diagnostic methods and need for updated epidemiological studies.…”
Section: Discussionsupporting
confidence: 89%
“…A review of 15 ASD studies in PWS found that children with PWS had high rates of restricted and repetitive behavior and impairment in social communication similar to general ASD populations (Bennett et al, ). A recent study found lower verbal and composite IQ scores, more social and communication impairments, more restricted behavior, and increased stereotypies in children with PWS + ASD compared to those with PWS only (Dykens et al, ). As none of these studies used the ABC as a measure, it would be difficult to compare these results with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with the larger type 1 deletion (Figure 1) have been reported to have better academic performance and intellectual abilities, and more compulsiveness when compared to type 2 deletion patients (69,70). Several other features are more common in mUPD individuals, such as post-term delivery, higher verbal IQ, psychosis and autism spectrum disorder (15,69,(71)(72)(73)(74)(75). On the other hand, mUPD patients are less likely to have the typical PWS facial appearance or hypopigmentation (16).…”
Section: Genotype-phenotype Relationships In Prader-willi Syndromementioning
confidence: 99%